The Role of the Reactive Oxygen Species Scavenger Agent, Astaxanthin, in the Protection of Cisplatin-Treated Patients Against Hearing Loss - Nan B; Gu X; Huang X (Dove Medical Press, 2019)
Benyu Nan,1,2 Xi Gu,3 Xinsheng Huang2 1Department of Otorhinolaryngology-Head and Neck Surgery, Wenzhou Medical University, Affiliated Hospital 2, Wenzhou 325000, People’s Republic of China; 2Department of Otorhinolaryngology-Head and Neck Surgery, Zhongshan Hospital, Fudan University, Shanghai 200030, People’s Republic of China; 3Department of Otolaryngology-Head and Neck Surgery, The First Affiliated Hospital of Fujian Medical University, Fuzhou 350000, People’s Republic of ChinaCorrespondence: Xinsheng HuangDepartment of Otorhinolaryngology-Head and Neck Surgery, Zhongshan Hospital, Fudan University, Fenglin Road 180, Xuhui District, Shanghai 200030, People’s Republic of ChinaTel +86 13681971739Fax +86 021-64041990Email huang.xinsheng@zs-hospital.sh.cnAbstract: Emerging evidence of significant hearing loss occurring shortly after cisplatin administration in cancer patients has stimulated research into the causes and treatment of this side effect. Although the aetiology of cisplatin-induced hearing loss (CIHL) remains unknown, an increasing body of research suggests that it is associated with excessive generation of intracellular reactive oxygen species (ROS) in the cochlea. Astaxanthin, a xanthophyll carotenoid, has powerful anti-oxidant, anti-inflammatory, and anti-apoptotic properties based on its unique cell membrane function, diverse biological activities, and ability to permeate the blood-brain barrier. In this review, we summarize the role of ROS in CIHL and the effect of astaxanthin on inhibiting ROS production. We focus on investigating the mechanism of action of astaxanthin in suppressing excessive production of ROS.Keywords: astaxanthin, oxidative stress, cisplatin, hearing loss